2012
DOI: 10.4103/0973-1075.105687
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes in patients living with stoma

Abstract: Background:Despite efforts to maintain the intestinal tissue and treat gastrointestinal disease, a large number of patients undergo ostomy surgery each year. Using stoma reduces the patient's quality of life (QOL) greatly. Although there are approximately 3000 patients in Iran; there is little information about the impact of stoma on their QOL.Aims:The study aims to evaluate QOL of stoma patients using a special measurement tool.Settings and Design:This survey was a cross-sectional study that was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
47
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 18 publications
14
47
2
6
Order By: Relevance
“…In our study, the environmental dimension was the highest mean score chosen by the respondents, followed by physical health, psychological, and social. Our findings are consistent with previous studies that found that the stoma patients had more difficulty participating in social activities (Dabirian et al, 2010;Anaraki et al, 2012). Swan (2011) and McMullen et al (2008) pointed out that the colostomy application might have a negative impact on the patients' quality of life with regards to both social and family relationships, travelling, physical activity, sexual function and finances.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In our study, the environmental dimension was the highest mean score chosen by the respondents, followed by physical health, psychological, and social. Our findings are consistent with previous studies that found that the stoma patients had more difficulty participating in social activities (Dabirian et al, 2010;Anaraki et al, 2012). Swan (2011) and McMullen et al (2008) pointed out that the colostomy application might have a negative impact on the patients' quality of life with regards to both social and family relationships, travelling, physical activity, sexual function and finances.…”
Section: Discussionsupporting
confidence: 83%
“…Satisfaction with their sexual relationship was chosen as the lowest item in relation to quality of life by most respondents. The findings of the study are consistent with previous studies that reported that stoma patients experienced a loss in their sexual activity after stoma surgery (Gemmill et al, 2010;Anaraki et al, 2012). This condition has resulted in low self-confidence of the respondents in performing sexual activities.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, health care professional must be knowledgeable to cater the patients physical and psychological educational needs (Anaraki et al, 2012). Previous literature also indicated that nurses can play significant role in physical, psychological, economical, social and many other aspects of care in colostomy patients provided they are adequately updated through in-service education related to colostomy care (Sinha, Goyal, Singh, & Rana, 2009).…”
Section: Introductionmentioning
confidence: 99%